Stage fright - Keene, Carolyn (Keene, Carolyn. Nancy Drew, girl detective, and the Hardy boys, undercover brothers, super mystery, 2012)
When a new Broadway musical is sabotaged by death threats and accidents that nearly kill an understudy, the Hardy brothers enlist the aid of Nancy Drew, whose likeness to the show's lead actress enables them to arrange an inside investigation.